The prioritization of open innovation determinants in banking - Tornjanski, Vesna; Marinkovic, Sanja; Levi Jaksic, Maja; Bogojevic Arsic, Vesna (Industrija, 2015)
The research scope of the paper is prioritization of open innovation determinants in banking industry using an integrated application of qualitative and quantitative methods in the evaluation process. The research methods were implemented to compound the depth of experts’ knowledge and experience on the one hand, and the precise mathematical reasoning, on the other, thus creating the objective and accurate basis for effective decision making. The overview of determinants of open innovations in banking industry has been obtained from the literature overview and the Delphi study conducted among 51 experts from banks in Serbia. Fifteen significant determinants within five dimensions were further evaluated through AHP decision-making method to prioritize them toward the development of the open innovation in banking. The research results show that effective application of open innovation in banking lies in formal reinforcement by management to integrate innovation into organizational policies and in designing dual structures that facilitate the initiation and implementation of an innovation, i.e. building an ambidextrous organization. The research findings and results introduced in this paper can be usefully applied and widely used by both academics and practitioners who are interested in applying the open innovation concept in banking industry.